Spices of the Pacific region with special reference to vanilla and ginger production: Challenges and the way forward: Vanilla and ginger production in the Pacific region - Kandiannan, K; Prasad, Shalendra; Banuve, Amena (Journal of Spices and Aromatic Crops, 2022)
The Pacific region (Oceania) is divided into four sub-regions (i) Australasia (Australia and New Zealand), (ii) Melanesia, (iii) Micronesia, and (iv) Polynesia and the population of this region is around 0.5% of the global population. There are 14 independent countries and 12 dependent overseas territories in Oceania. Most of the countries are smaller in size, less developed (except Australia and New Zealand), remotely placed and vulnerable to natural calamities. Spices are mostly introduced crops to this region. Turmeric was the earliest spice introduced to this region. The Missionaries and Europeans who colonized these regions introduced many other spices. British introduced ginger to Australia during 1788. Fiji is an important south pacific country, where Fiji-Indians consume considerable amount of spices. Black pepper and vanilla were introduced during 1880’s; ginger before 1890 (Probably from Australia), cardamom, nutmeg and clove during 1930’s to Fiji. The FAO statistics provide data on spices production from ten Oceanica countries with a total production of 618, 914 tonnes which translates to 0.3% of the global spices production. The spice crops of the region are chillies, onion, garlic, ginger, turmeric, vanilla, nutmeg and coriander. Other spices like tamarind, mango, (tender mango) cinnamon, curry leaf, herbal spices are produced in small scale and exported within the region. Spice crops like clove, allspice, black pepper, small cardamom are also grown by a few individuals in limited number. There is not much research work on spices except for ginger in Australia and a few on vanilla diseases from the Pacific region. This review provides the status of spices in the Pacific region focusing on ginger and vanilla which helps to understand the status of spices of Oceania. The information complied here may help in designing strategies for enhancing spice production and trade, which can positively influence the economy of the region.